2007
DOI: 10.1590/s1676-24442007000100012
|View full text |Cite
|
Sign up to set email alerts
|

Microdissecção e captura a laser na investigação do gene TP53 em tecidos incluídos em parafina

Abstract: Microdissecção e captura a laser na investigação do gene TP53 em tecidos incluídos em parafi na Laser-capture microdissection for TP53 gene analysis in paraffi n-embedded tissues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The initial PCR products were diluted and re-amplified in six In general, desoxyribonucleic acid (DNA) recovered from formalin-fixed paraffin-embedded tissues is highly degraded (10) and may be unsuitable for most molecular techniques such as polymerase chain reaction (PCR). Although some studies have shown that PCR can be successfully performed with DNA recovered from formalin-fixed paraffin-embedded-tissues (2,3,5,9) , results have still been limited in some laboratories.…”
Section: Resumo Abstractmentioning
confidence: 99%
“…The initial PCR products were diluted and re-amplified in six In general, desoxyribonucleic acid (DNA) recovered from formalin-fixed paraffin-embedded tissues is highly degraded (10) and may be unsuitable for most molecular techniques such as polymerase chain reaction (PCR). Although some studies have shown that PCR can be successfully performed with DNA recovered from formalin-fixed paraffin-embedded-tissues (2,3,5,9) , results have still been limited in some laboratories.…”
Section: Resumo Abstractmentioning
confidence: 99%